2007
DOI: 10.1101/gr.6328907
|View full text |Cite
|
Sign up to set email alerts
|

Expression evolution in yeast genes of single-input modules is mainly due to changes in trans-acting factors

Abstract: Both cis-and trans-regulatory mutations contribute to gene expression divergence within and between species. To estimate their relative contributions, we examined two yeast strains, BY (a laboratory strain) and RM (a wild strain), for their gene-expression divergence by microarray. Using these data and published ChIP-chip data, we obtained a set of single-regulator-regulated genes that showed expression divergence between BY and RM. We randomly selected 50 of these genes for further study. We developed a step-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…These studies suggest that the apparent regulatory variation, as opposed to individual target gene expression, is more constrained. In other studies of cis and trans variation, cis variation for a target gene varies to greater magnitude than trans regulatory variation, which is, however, multigenic if the variation is great enough to be detected (122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134). The multigenic lowmagnitude transacting effects on gene expression, the mutation accumulation results, and the finding that members of protein complexes that exhibit dosage effects have limited variation form a consistent set of observations suggesting that there is a generalized constraint on regulatory variation.…”
Section: Implications For Quantitative Traitsmentioning
confidence: 78%
“…These studies suggest that the apparent regulatory variation, as opposed to individual target gene expression, is more constrained. In other studies of cis and trans variation, cis variation for a target gene varies to greater magnitude than trans regulatory variation, which is, however, multigenic if the variation is great enough to be detected (122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134). The multigenic lowmagnitude transacting effects on gene expression, the mutation accumulation results, and the finding that members of protein complexes that exhibit dosage effects have limited variation form a consistent set of observations suggesting that there is a generalized constraint on regulatory variation.…”
Section: Implications For Quantitative Traitsmentioning
confidence: 78%
“…By integrating transcriptional profiling and linkage analysis, Hubner et al (7) have shown that 35-40% of the eQTLs between two mouse strains were regulated in cis. In yeast the proportion of cis eQTL from different studies ranges from 10% to 25% (1,9,25). The differences may, to some degree, depend on the level of divergence analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…(cis regulation refers to the control of expression by the gene itself whereas trans regulation refers to the influence of the genetic background.) Many studies have addressed this question at various levels of divergence (1)(2)(3)(4)(5)(6)(7)(8)(9). For example, one may measure the expressions of two alleles at the locus of interest in a common genetic background (usually F 1 s) (1,2,5).…”
mentioning
confidence: 99%
“…Recent work on the evolution of gene expression has focused largely on local regulatory elements (cis-regulation; Gompel et al 2005;Wittkopp 2006) or on the expression/activity of proteins that interact with such sequences (trans-regulation; Wittkopp et al 2004;Wang et al 2007). These DNA-transcription factor interactions, however, compose only one component of gene regulation.…”
mentioning
confidence: 99%